2007
DOI: 10.1002/ccd.21136
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in vivo acute stent recoil between the bioabsorbable everolimus‐eluting coronary stent and the everolimus‐eluting cobalt chromium coronary stent: Insights from the ABSORB and SPIRIT trials

Abstract: In vivo acute stent recoil of the BVS is slightly larger but insignificantly different from that of the EES, implying that the BVS may have good radial strength similar to the metallic stent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
2
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 139 publications
(95 citation statements)
references
References 22 publications
3
86
2
4
Order By: Relevance
“…Tanimoto et al 9 compararam o SVB com o EES e constataram que o percentual de retração aguda foi de 6,9 ± 7,0% no grupo SVB e 4,3 ± 7,1% no grupo EES (P = 0,25). Onuma et al 10 compararam a retração aguda de duas versões do SVB ABSORB (revision 1.0 e revision 1.1) com o stent XIENCE ® V e descobriram que a retração aguda do SVB 1.1 foi um pouco maior do que os EES metálicos (EES: 4,3 ± 7,1%; SVB 1.0: 6,9 ± 7,0%; SVB 1.1: 6,7 ± 6,4%; P = 0,22).…”
Section: Discussionunclassified
“…Tanimoto et al 9 compararam o SVB com o EES e constataram que o percentual de retração aguda foi de 6,9 ± 7,0% no grupo SVB e 4,3 ± 7,1% no grupo EES (P = 0,25). Onuma et al 10 compararam a retração aguda de duas versões do SVB ABSORB (revision 1.0 e revision 1.1) com o stent XIENCE ® V e descobriram que a retração aguda do SVB 1.1 foi um pouco maior do que os EES metálicos (EES: 4,3 ± 7,1%; SVB 1.0: 6,9 ± 7,0%; SVB 1.1: 6,7 ± 6,4%; P = 0,22).…”
Section: Discussionunclassified
“…In particular, the ABSORB cohort A trial, using BVS revision 1.0, demonstrated a slightly higher acute recoil with BVS than with metallic stents. 67 More recently, Onuma et al 68 showed that, among 88 patients enrolled in the ABSORB cohort B trial, absolute recoil of BVS 1.1 was numerically higher than that of metallic EES and similar to that of BVS 1.0, but the differences did not reach statistical significance. In their multivariate regression model, high absolute recoil was predicted by high balloon/artery ratio.…”
Section: Disclosuresmentioning
confidence: 99%
“…Of note, the stent/scaffold type was not a predictor of acute recoil. 67 Finally, a recent study 69 analyzing clinical data from the first 450 patients enrolled in ABSORB EXTEND has demonstrated low rates of ischemia-driven MACE (4.2%) and target vessel failure (4.7%) at 12 months. Of note, the cases of device failure were principally caused by dislodgement (0.67%) and to late scaffold thrombosis (0.89%).…”
Section: Disclosuresmentioning
confidence: 99%
“…Encouragingly, studies also indicated that the BVS has comparable acute vessel recoil to the EES, inferring similar initial radial strength. 56, 57 Although the scaffold is radiolucent, 2 platinum markers at each end allow easy visualization on angiography and other imaging modalities.…”
Section: Onuma Y Et Almentioning
confidence: 99%